2013
DOI: 10.5194/acp-13-5173-2013
|View full text |Cite
|
Sign up to set email alerts
|

Source apportionment of fine PM and sub-micron particle number concentrations at a regional background site in the western Mediterranean: a 2.5 year study

Abstract: The chemical composition and sources of ambient fine particulate matter (PM1) over a period of 2.5 years for a regional background site in the western Mediterranean are presented in this work. Furthermore, sub-micron particle number concentrations and the sources of these particles are also presented. The mean PM1 concentration for the measurement period was 8.9 μg m−3, with organic matter (OM) and sulphate comprising most of the mass (3.2 and 1.5 μg m−3 respectively… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 36 publications
8
27
0
Order By: Relevance
“…New particle formation (NPF) events have been widely observed in the atmosphere in different environments from remote areas at high altitude or latitude to polluted environments in different climates (Pey et al, 2008;Manninen et al, 2010;Yli-Juuti et al, 2011;Cusack et al, 2013). However, the exact mechanism and chemical species involved in the NPF process are not fully identified, especially regarding the diversity of environments to consider.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…New particle formation (NPF) events have been widely observed in the atmosphere in different environments from remote areas at high altitude or latitude to polluted environments in different climates (Pey et al, 2008;Manninen et al, 2010;Yli-Juuti et al, 2011;Cusack et al, 2013). However, the exact mechanism and chemical species involved in the NPF process are not fully identified, especially regarding the diversity of environments to consider.…”
Section: Introductionmentioning
confidence: 99%
“…Although the Mediterranean area is particularly sensitive to the future evolution of atmospheric pollutants and climate change, only a few studies related to NPF in this area have been reported so far. Intensive campaigns were conducted on the eastern Spanish coast, in Barcelona and at the Montseny site (Pey et al, 2008;Cusack et al, 2013), while long-term measurements are performed at the Finokalia (Crete) station (Kalivitis et al, 2008(Kalivitis et al, , 2015Manninen et al, 2010;Pikridas et al, 2012), where NPF event days are close to 30 %. The Mediterranean Basin is at the cross section of many different influences: there is a strong anthropogenic influence from densely populated coastal zones, in addition to marine and dust sources, as well as with emissions from Mediterranean forests and shrublands that emit both terpenes and isoprene.…”
Section: Introductionmentioning
confidence: 99%
“…3). By comparing the mean value of the PM 1 daily concentrations registered in Viggiano with those reported in other studies, it can be observed that it is generally lower than those found at other sites (Cusack et al, 2013;Onat et al, 2013;Perrone et al, 2014;Theodosi et al, 2011;Caggiano et al, 2010;Pérez et al, 2008a, b;Marenco et al, 2006;Gomišček et al, 2004) and, in particular, it is lower than the PM 1 concentration mean value (11.0±5.1 µg m −3 ) measured close to the COVA plant from July to November 2011 (Trippetta et al, 2013). Regarding the latter, this could be due to the combination of two factors: the geographical position of Viggiano with respect to the COVA plant, and the wind features of the area.…”
Section: Meteorologymentioning
confidence: 91%
“…The presence of K may also suggest the influence of the biomass and wood burning in this component. In fact, K is the most common inorganic species used to trace this kind of source (Cusack et al, 2013;Kim et al, 2010). Therefore, PC 1 identifies the PM 1 crustal fraction, with a minor contribution of biomass and wood burning.…”
Section: Principal Component Analysismentioning
confidence: 99%
“…The summer environmental category urban_TSP, where PM 1-2.5 also depended on PM 1 , included measurement sites heavily influenced by exhaust emission from traffic and, thus, dominant PM 1 source (for instance: Guigliano et al, 2005;Pérez et al, 2010;Ondráček et al, 2011;Cusack et al, 2013). On the other hand, the second summer urban (urban_PM 10 ) environment represented only one measurement site directly situated closed to university botanical garden (35,000 m 2 ).…”
Section: Multiple Linear Regression (Mlr) Analysismentioning
confidence: 99%